INTEGRATION OF BIOTECHNOLOGY INTO THE CIRCULAR ECONOMY - Yerokhin, Володимир; Stets , Максим (Biota. Human. Technology, 2024)
Objective. The article emphasises the importance of the study because of the effectiveness and representativeness of the integration of biotechnology into the circular economy, as it provides a non-linear approach that promotes additional profits and protects the environment from environmental disasters. Methodology. The methods used include: a) biodegradation and biodecomposition using biomaterials such as organic waste, biopolymers and bioplastics, which are studied using biochemical tests, mass spectrometry and molecular biological methods; b) biosynthesis and biorefining using living organisms such as bacteria, fungi and algae, which are genetically modified to increase their productivity and sustainability; c) bioremediation for the study of biomaterials and microorganisms that clean up contaminated sites, using high-performance liquid chromatography and molecular genetic methods to assess efficacy and environmental safety; d) bioengineering, which includes high-throughput genome editing methods. Scientific novelty. The core principles of the circular economy include renewability (repair and reuse of products), differentiation (selection of materials whose decomposition is faster and safer), environmentalism (use of clean energy sources that increase the sustainability of systems) and culturalism (spreading the environmental paradigm to change consumer behaviour). Conclusions. The integration of biotechnology into the circular economy is of particular importance in the context of the current environmental situation and the need to introduce a non-linear economy that meets the modern culture of consumption. The main prospects are the improvement of existing methods, innovative solutions and interdisciplinary approaches. Further research should focus on improving biodegradation processes and introducing new materials, which will help to intensify interaction between academic institutions, industrial companies and other stakeholders. Biotechnology in the context of the circular economy has significant potential for sustainable development, environmental protection, and intensification of scientific progress through the development of new methodologies, techniques, and integrative research projects.